2010
DOI: 10.1002/jcc.21667
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of static first hyperpolarizability of donor–acceptor substituted (E)‐benzaldehyde phenylhydrazone

Abstract: Various hybrid functionals (B3LYP, B97-2, PBE0, BMK, BH&HLYP, CAM-B3LYP, and LC-ωPBE) implemented in density functional theory were applied to give estimate of static first hyperpolarizabilty (β(0)) of (E)-benzaldehyde phenylhydrazone designated as (E)-BPH. Against those of MP2 computations as a function of the underlying density functional, good agreement was obtained with the BH&HLYP and CAM-B3LYP functionals. The LC-ωPBE functional and the B3LYP, PBE0, B97-2, and BMK functionals underestimated and overestim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…This Table illustrates the improvement of tuned over standard LC-DFT when comparing with static β tot values calculated by the MP2 method, which has been shown to produce reasonably accurate molecular hyperpolarizabilities. 22,40,67,[76][77][78] The qualitative observations that can be drawn from Table 5 are similar to those obtained when using experimental data as reference; LC-DFT tends to underestimate hyperpolarizabilities, the tuning procedure roughly halves this error, and the improvement is more noticeable in polar environments. We also note that, although MP2 tends to somehow overshoot β ijk values compared to coupled cluster calculations, this effect is usually small when using large enough basis sets, similar to the ones used here (see, e.g., Refs.…”
Section: Computational Detailssupporting
confidence: 76%
“…This Table illustrates the improvement of tuned over standard LC-DFT when comparing with static β tot values calculated by the MP2 method, which has been shown to produce reasonably accurate molecular hyperpolarizabilities. 22,40,67,[76][77][78] The qualitative observations that can be drawn from Table 5 are similar to those obtained when using experimental data as reference; LC-DFT tends to underestimate hyperpolarizabilities, the tuning procedure roughly halves this error, and the improvement is more noticeable in polar environments. We also note that, although MP2 tends to somehow overshoot β ijk values compared to coupled cluster calculations, this effect is usually small when using large enough basis sets, similar to the ones used here (see, e.g., Refs.…”
Section: Computational Detailssupporting
confidence: 76%
“…). In a very recent paper published by Lu,83 where a computational study of static first hyperpolarizability of donor–acceptor substituted ( E )‐benzaldehyde phenylhydrazone was reported using various DFT functional and the MP2 level of theory used as reference result, the BH and HLYP and CAM‐B3LYP functional were recommended as the best choice for the estimation of molecular nonlinearity of hydrazones. However, in this study for PDES decamer the PBE1PBE functional was found very suitable for the calculation of β.…”
Section: Resultsmentioning
confidence: 99%
“…[9,10,88,90] The rather modest 6-31 + G* basis set was demonstrated to be suitable for estimating the relative hyperpolarizabilities of D/A p-conjugated systems. [10,39,91,92] Using experimental data for an assessment can be problematic due to solvent effects, [93] and potentially due to an implicit use of different conventions. To assess the accuracy of the various DFT calculations, a comparison is made with MP2 data.…”
Section: Hyperpolarizability B Kmentioning
confidence: 99%